2022
DOI: 10.1371/journal.pone.0271483
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome versus acute myocarditis in young adults–value of speckle tracking echocardiography

Abstract: Purpose Comparing myocarditis with an acute coronary syndrome (ACS)-like presentation and acute myocardial infarction (AMI) poses an important clinical challenge. The purpose of the study was to investigate the diagnostic value of the clinical, laboratory and especially echocardiographic characteristics including speckle tracking echocardiography (STE) of patients with ACS-like myocarditis and AMI. Methods We conducted a retrospective analysis comparing 69 symptomatic patients (≤ 45 years old), hospitalized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…Notably, when considering myocarditis caused by ICIs, it is important to also consider other potential diagnoses, which may include acute coronary syndrome, stress cardiomyopathy and viral myocarditis. These conditions can be challenging to accurately diagnose based solely on clinical presentation (39)(40)(41). Comprehensive coronary CT angiography, invasive coronary angiography, electrocardiogram, infection indicators and patient history can help clinicians make a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when considering myocarditis caused by ICIs, it is important to also consider other potential diagnoses, which may include acute coronary syndrome, stress cardiomyopathy and viral myocarditis. These conditions can be challenging to accurately diagnose based solely on clinical presentation (39)(40)(41). Comprehensive coronary CT angiography, invasive coronary angiography, electrocardiogram, infection indicators and patient history can help clinicians make a differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This makes cardiac magnetic resonance (CMR) examination the reference standard in diagnosing acute myocarditis. Its application is demonstrated by CMR's ability to identify myocardial edema and inflammation non-invasively [32,37]. The establishment of the diagnosis of myocarditis uses MRI and/or biopsy; however, due to limitations, the use of additional diagnoses using CMR and biopsy could not be performed in our study.…”
Section: Analysis Of Relationship Of Clinical Characteristics To Inci...mentioning
confidence: 99%
“…Our findings showed that most patients had preserved LVEFs, non-dilated LVs, and normal E/A ratios. However, LVEF assessment is less able to show subtle myocardial dysfunction [32]. Therefore, in the assessment of the LV function, we included the GLS assessment, which was indicated by a decrease in the LV function in most of the samples, with a mean of 12.92 + 4.99.…”
Section: Subanalysis Of the Echocardiographic Profile Of Severe Covid...mentioning
confidence: 99%
See 1 more Smart Citation
“…O diagnóstico final de miocardite só é possível através da EMB, que ainda é o padrão ouro diagnóstico, mas devido ao seu caráter invasivo, baixa disponibilidade e pequeno número de equipes multidisciplinares com competências complementares no procedimento de EMB, extremamente limitado na prática clínica (WIECZORKIEWICZ P, et al, 2022).…”
Section: Quadro Clínico E Diagnósticounclassified